2017
DOI: 10.1371/journal.pone.0181342
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of highly metastatic KRAS mutant lung cancer cell sublines in long-term three-dimensional low attachment cultures

Abstract: Decreased cell-substratum adhesion is crucially involved in metastasis. Previous studies demonstrated that lung cancer with floating cell clusters in histology is more likely to develop metastasis. In the present study, we investigated whether cancer cells in long-term, three-dimensional low attachment cultures acquire high metastatic potential; these cells were then used to examine the mechanisms underlying metastasis. Two KRAS-mutated adenocarcinoma cell lines (A549 and H441) were cultured and selected on ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…S3E-S3G). On the other hand, MYC silencing with a validated shRNA (33,34) recapitulated the phenotype of Pgc1a expression in cell area, p-MLC2, and invasive growth ( Supplementary Fig. S3H-S3L).…”
Section: Resultsmentioning
confidence: 92%
“…S3E-S3G). On the other hand, MYC silencing with a validated shRNA (33,34) recapitulated the phenotype of Pgc1a expression in cell area, p-MLC2, and invasive growth ( Supplementary Fig. S3H-S3L).…”
Section: Resultsmentioning
confidence: 92%
“…4d). To ascertain if MYC silencing recapitulated the effect of PML inhibition, we used a validated shRNA targeting this oncogene (sh42) [42,43] and confirmed that MYC silencing resulted in increased p27 levels ( Fig. 4e and Supplementary Fig.…”
Section: Myc and Pim1 Are Regulated By Pml In Tnbcmentioning
confidence: 90%
“…The absence of the RNA and reverse transcriptase in these cell lines confirmed that the cell lines are negative for HIV-1 and HIV-2. The luciferase gene was introduced into these cell lines by the lentiviral vector [ 33 ], which may be associated with the detection by PCR. Because HIV-1 and HIV-2 are highly pathogenic and must be handled under biosafety level 3 (BSL3), such cell lines are not received and distributed from our JCRB Cell Bank.…”
Section: Resultsmentioning
confidence: 99%